2013
DOI: 10.1080/09640568.2013.859129
|View full text |Cite
|
Sign up to set email alerts
|

Objective exposure to road traffic noise, noise annoyance and self-rated poor health – framing the relationship between noise and health as a matter of multiple stressors and resources in urban neighbourhoods

Abstract: 2013):Objective exposure to road traffic noise, noise annoyance and self-rated poor healthframing the relationship between noise and health as a matter of multiple stressors and resources in urban neighbourhoods, Journal of Environmental Planning and Management, Objective exposure to road traffic noise, noise annoyance and selfrated poor health -framing the relationship between noise and health as a matter of multiple stressors and resources in urban neighbourhoodsBorrowing from concepts of socio-environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…Some studies indicated that annoyance caused by traffic noise was a modifier of the association between noise level and health. [ 124 125 ] However, this correlation should be interpreted with caution. Individual noise exposure largely depends on housing conditions and lifestyle,[ 126 ] and an equivalent sound level (e.g., L night ) was chosen for mainly practical reasons.…”
Section: Nonauditory Effects Of Noisementioning
confidence: 94%
See 2 more Smart Citations
“…Some studies indicated that annoyance caused by traffic noise was a modifier of the association between noise level and health. [ 124 125 ] However, this correlation should be interpreted with caution. Individual noise exposure largely depends on housing conditions and lifestyle,[ 126 ] and an equivalent sound level (e.g., L night ) was chosen for mainly practical reasons.…”
Section: Nonauditory Effects Of Noisementioning
confidence: 94%
“…For this review, the literature published during the period from August 2011 to December 2013 was searched. Sixty peer-reviewed journal publications were identified,[ 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 107 108 109 110 111 112 113 114 115 116 117 118 119 120 121 122 123 124 125 126 127 ] which indicated that an impressive amount of progress in the field was made during the last 3 years. Many results were published based on data analyses of existing or ongoing cohort studies.…”
Section: Nonauditory Effects Of Noisementioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that exposure to intractable environmental stressors, such as noise, require the use of high levels of an individual’s personal resource in order to cope [ 52 ]. If unable to draw on sufficient resources this may undermine the sense of security with the home environment.…”
Section: Discussionmentioning
confidence: 99%
“…As well, some studies referred to well-being-related impacts of e.g., aircraft noise or railways [ 28 , 35 , 36 , 37 , 38 , 39 ] but these were not considered applicable for road traffic. A range of noise studies provide dose-response relations between transport noise levels and noise annoyance which sometimes are highly significant [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], but as noise annoyance mainly contributes to evaluative and objective well-being, it may not adequately reflect the multi-faceted concept of general subjective well-being [ 15 , 46 , 47 ]. Also, noise annoyance is often used in HIA as an independent health outcome and URGENCHE-related HIA work on transport interventions has also applied annoyance accordingly [ 7 , 48 ].…”
Section: Methodsmentioning
confidence: 99%